Ecological features of the flowers of Aesculus hippocastanum L. and characteristics of Aesculus L. pollen seasons under the conditions of central-eastern Poland - Elżbieta Weryszko-Chmielewska; Maria Tietze; Magdalena Michońska (Acta Agrobotanica, 2012)
The content of Aesculus pollen in aeroplankton of Lublin, located in central-eastern Poland, was studied during the period 2001–2012. The volumetric method was used for the study. The following parameters were determined: start, end, and duration of the pollen season, days of maximum concentration, and total annual pollen counts. Correlation coefficients were calculated between the start of the pollen season and meteorological parameters. The study showed that during the period 2007–2012 the onset of the Aesculus pollen season occurred on average 4 days earlier than in the years 2001–2006. The total annual pollen counts were in the range of 53–271, with an average number of 117. The average pollen counts did not differ significantly in the first and second year of a 6-year period of the study. The analysis of the correlation coefficients showed that there were significant positive correlations only between the season start date and minimum temperature of the first decade of May. The highest Aesculus pollen concentration occurred between 6 and 22 May. The flowers of A. hippocastanum demonstrate an ambophilous pollination strategy due to partial insect and wind pollination.